Design and Kinematics Performance Analysis of an Equivalent 3-PzPxS Parallel Mechanism - Yeping Lü; Yong Xu; Wei Liang Song; Zheng Liang; Yong Liu (Jixie chuandong)
In order to meet the requirements of the configuration innovation of the multi-axis linkage processing platform， a new type of 2R1T 3-PzPxS parallel mechanism is synthesized， which contains a planar pantograph structure unit in the branching chain. The branch chain configuration is proposed and optimized to verify the degree of freedom of the mechanism. The forward and inverse analytical solutions of the mechanism position are derived and obtained， which is convenient for subsequent motion planning and control. Based on the Jacobian matrix of mechanism， the parameter conditions resulting in positive kinematic singularities are confirmed. After obtaining the workspace of the mechanism by using the boundary search method， it is determined that the mechanism has a large rotational capacity. The related results lay a theoretical foundation for the research of high efficiency NC machining center.